2012
DOI: 10.1175/mwr-d-10-05021.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Beta Shear on Simulated Tropical Cyclones

Abstract: Through cloud-resolving simulations, this study examines the effect of ß on the evolution of tropical cyclones (TCs). It is found that the TC simulated on a /3 plane with variable Coriolis parameter/is weaker in intensity but larger in size and strength than the TC simulated on an/plane with constant/. Such differences result mainly from the effect of the ß shear rather than from the variation of/due to the latitudinal change of the TC position, as illustrated in a three-stage conceptual model developed herein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 50 publications
4
61
0
Order By: Relevance
“…The model has been adapted for use with idealized initial conditions to permit careful control of the initial-value experiments that enables us to examine the physical mechanisms associated with TC structural changes. WRF has been used by many previous sensitivity studies that explore mechanisms concerning TC size and intensity changes (e.g., Frank and Ritchie 2001;HL09;Fang and Zhang 2012;Mallard et al 2013). …”
Section: Methodology a Model Descriptionmentioning
confidence: 99%
“…The model has been adapted for use with idealized initial conditions to permit careful control of the initial-value experiments that enables us to examine the physical mechanisms associated with TC structural changes. WRF has been used by many previous sensitivity studies that explore mechanisms concerning TC size and intensity changes (e.g., Frank and Ritchie 2001;HL09;Fang and Zhang 2012;Mallard et al 2013). …”
Section: Methodology a Model Descriptionmentioning
confidence: 99%
“…Because many external environmental factors affect the outer region of TCs, TC size is affected more by the number of external factors than TC intensity. In fact, many previous studies have indicated that various external factors affect TC size; examples are ocean basins and seasons (e.g., Merrill 1984;Chan and Chan 2012;Knaff et al 2014), synoptic environments (e.g., Liu and Chan 2002;Yuan et al 2007), β-effect (Fang and Zhang 2012), and latitude (e.g., Weatherford and Gray 1988a, b;Kimball and Mulekar 2004). The involvement of so many external environmental factors complicates the quantitative evaluation of the relationship between TC size and those factors.…”
Section: Significance and Difficulty Of The Study On The Size Of Tropmentioning
confidence: 99%
“…This inflow is likely to enhance the boundary layer convergence and trigger convection in the inner-core region of TCs. Fang and Zhang (2012) suggested that the development of new convection preceding SEF might be facilitated with a frontlike feature in the low-level equivalent potential temperature field. The sharpening of equivalent potential temperature gradient was due to the evaporative cooling of rainwater under a wavenumber-1 stratiform cloud deck induced by b shear.…”
Section: Introductionmentioning
confidence: 99%